HUBUNGAN KUALITAS PELAYANAN KEFARMASIAN TERHADAP KEPUASAN PASIEN DI PUSKESMAS NGANTRU KABUPATEN TULUNGAGUNG TAHUN 2025 - Sugeng Walujo, Djembor (FACULTY OF PHARMACY, INSTITUT ILMU KESEHATAN BHAKTI WIYATA, 2025)
Background: High-quality, optimal health services are essential for community well-being. Pharmaceutical service standards guide pharmacy staff in delivering these services, minimizing the risk of medication errors. Objective: A 2025 study aimed to explore the correlation between the quality of pharmaceutical services and patient satisfaction at the Ngantru Regency Tulungagung Public Health Center. Methods: The study employed an analytical observational method with a cross-sectional design. Ninety-seven patients from the health center, meeting specific inclusion and exclusion criteria, were selected using purposive sampling. Data were collected via questionnaires, with the quality of pharmaceutical services as the independent variable and patient satisfaction as the dependent variable. Chi-square tests were used for data analysis. Result: The results indicated that 80.4% of respondents rated the pharmaceutical services as very good, while 19.6% rated them as good. Additionally, 69.1% of respondents reported being very satisfied with the services, and 30.9% reported being satisfied. The chi-square test revealed a statistically significant relationship (p < 0.05) between the quality of pharmaceutical services and patient satisfaction at the Ngantru Health Center. Conclusions: The results of this study can be described that maximum efforts in pharmaceutical services at Ngantru Health Center provide support for community satisfaction in health services. This effort is to provide assurance that pharmaceutical services are carried out optimally so that patients get the best service in the health sector.